Occurrence of parasitic infections in ponies of tarai region, Uttar Pradesh - SENGUPTA, P P; YADAV, M P (The Indian Journal of Animal Sciences, 2013)
A study of seasonal incidence of parasites in pony mares in tarai area of Uttar Pradesh was carried out. No deworming practice was reported before this study. The animals were maintained on pasture grazing. The amplitude of the parasitic infeCtion was studied by faecal samples and blood. smear examination. During the study period, Strongylus sp. dominated in the rate of infection with highest of 64.52% in winter followed by Gastrodiscus aegyptiacus with 30.90% in summer and Trichonema sp. with 17.74% in winter. Besides, Trichostrongylus, Strongyloides westeri, Dictyocaulus arnfieldi, Parascaris equorum and Oxyuris equi were also recorded. Coproculture revealed Strongylus equinus, S. edentatus, S. vulgaris,Gyalocephalus, Triodontophorus and Oesophagodontus sp. larva.